Stephen versus Stephanie? Does Gender Matter for Peer-to-Peer Career Advice - Grace Lordan; Warn N. Lekfuangfu (Institute of Labor Economics (IZA), 2023)
Occupational segregation is one of the major causes of the gender pay gap. We probe the possibility that individual beliefs regarding gender stereotypes established in childhood contribute to gendered sorting. Using an experiment with two vignette designs, which was carried out in schools in the UK, we consider whether students aged 15-16 years recommend that a fictitious peer pursue different college majors and career paths simply because of their gender. We find strong evidence that this is the case. The within-majors treatment design shows that our respondents are 11 percentage points more likely to recommend corporate law to a male peer. The across-majors design reveals that students presented with a male fictitious peer tend to recommend degrees that have lower shares of females to males.
Keywords: J24; 330; sorting; gender stereotype; gender; vignette design; occupational choice; college major choice